Environmental dimensions and administrative mechanisms for the territory planning in Algeria, between theory and reality. (Journal of Planner and Development, 2021)
In front of the serious deterioration of the elements of the environment, new convictions arose the need to integrate into the global environmental concerns as being one and the issue of shared responsibility and the impact of this conviction, the evolution of the environment protection law in many countries, including Algeria. Due to the multiplicity of perceptions about the environmental result of multiple scientific disciplines, the legislative concept emerged to protect the environment, which includes prevention and rational management and conservation and restoration and repair. Environmental planning for the various governments and countries aims to avert disasters and achieve the highest environmental levels of security for the population, are extremely important goals require a protective role senior management, and the view of the great difficulty in preventing ecological damage, requiring the administration drafting legal system to deter violations and behaviors harmful to the environment as a first step, then Jump to the inclusion of responsibility to compensate for environmental damage as a second step. Today facing Algeria sensitive environmental challenges linked to economic development requirements and future options in the management and exploitation of private, including energy, water and land sources of natural resources, the environmental situation in the embarrassing situation threatens the ecosystem in the future, despite the presence of a legal arsenal, mechanisms and protective in the field of environmental protection remains, there is no environmental degradation continues this has been confirmed by official reports about the environment in Algeria.